2014
DOI: 10.3389/fneur.2014.00203
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Response Properties of Inferior Colliculus Neurons Relating to Tinnitus

Abstract: Tinnitus is often identified in animal models by using the gap prepulse inhibition of acoustic startle. Impaired gap detection following acoustic over-exposure (AOE) is thought to be caused by tinnitus “filling in” the gap, thus, reducing its salience. This presumably involves altered perception, and could conceivably be caused by changes at the level of the neocortex, i.e., cortical reorganization. Alternatively, reduced gap detection ability might reflect poorer temporal processing in the brainstem, caused b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 69 publications
2
22
0
Order By: Relevance
“…Here, we found that there were some increases in neural gap detection thresholds (in response to BBN) 2 h following sodium salicylate administration. This was consistent with the results of Berger et al (2014) in the inferior colliculus following noise exposure, as well as Deng et al (2010), who demonstrated increases in auditory cortex MGDTs following salicylate administration in rats. However, there was only one GP with minimum neural gap detection thresholds of greater than 50 ms, thereby suggesting that, for the majority of GPs, their temporal acuity was not affected to an extent that they would no longer be able to perform the behavioural task.…”
Section: Alterations In Gap Detection Ability Following Salicylate Adsupporting
confidence: 92%
See 4 more Smart Citations
“…Here, we found that there were some increases in neural gap detection thresholds (in response to BBN) 2 h following sodium salicylate administration. This was consistent with the results of Berger et al (2014) in the inferior colliculus following noise exposure, as well as Deng et al (2010), who demonstrated increases in auditory cortex MGDTs following salicylate administration in rats. However, there was only one GP with minimum neural gap detection thresholds of greater than 50 ms, thereby suggesting that, for the majority of GPs, their temporal acuity was not affected to an extent that they would no longer be able to perform the behavioural task.…”
Section: Alterations In Gap Detection Ability Following Salicylate Adsupporting
confidence: 92%
“…This was consistent with the results of Berger et al . () in the inferior colliculus following noise exposure, as well as Deng et al . (), who demonstrated increases in auditory cortex MGDTs following salicylate administration in rats.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations